Gas diffusion layer/flow-field unified membrane-electrode assembly in fuel cell using graphene foam. (10th November 2019) - Park, Ji Eun; Lim, Jongkoo; Lim, Myung Su; Kim, Sungjun; Kim, Ok-Hee; Lee, Dong Woog; Lee, Ji Hyun; Cho, Yong-Hun; Sung, Yung-Eun
Abstract: The integration of a gas diffusion layer with a flow-field is essential for enhancing the polymer electrolyte membrane fuel cell performance. This is achieved by exploiting the ability of a gas diffusion layer-flow-field combination to decrease the size of the reactant pathway and the thickness of the membrane-electrode assembly, thereby reducing electrical and mass transport resistance. This study proposes a unified membrane-electrode assembly that incorporates graphene foam that functions as both a flow-field and a gas diffusion layer. The unified membrane-electrode assembly exhibits higher performance than conventional membrane-electrode assembly on overall current densities region, which is attributed to the increased the pressure drop. Furthermore, its estimated volume power density can be increased because of the 82% decrease in its thickness. Also, the simulation results show that this design enhances the exchange current density due to pressure drop in the graphene foam. Graphical abstract: Image 1 Highlights: Unified MEA using graphene-foam that functions as flow-field and GDL is prepared. Unified MEA enhances cell performance and volume power density by 8.2 times. Simulation results exhibits that unified MEA improved exchange current density. This enhancement is attributed to the increased internal pressure.